The Catechumenate in Late Antique Africa (4th -6th centuries) : Augustine of Hippo, his Contemporaries and Early Reception - Pignot, Matthieu, (Vigiliae Christianae, Supplements ;, 2020)
In The Catechumenate in Late Antique Africa (4th-6th centuries) Matthieu Pignot explores how individuals became Christian in ancient North Africa. Before baptism, converts first became catechumens and spent a significant time of gradual integration into the community through rituals and teaching. This book provides the first historical study of this process in African sources, from Augustine of Hippo, to canon of councils, anonymous sermons and 6th-century letters. Pignot shows that practices varied more than is generally assumed and that catechumens, because of their liminal position, were a disputed and essential group in the development of Christian communities until the 6th century at least. This book demonstrates that the catechumenate is key to understanding the processes of Christianisation and conversion in the West.